Studi Zat Anorganik dan Keasaman Kayu Jati (Tectona grandis) Hutan Rakyat Kulon Progo - , RUDY NUR HIDAYAH, Dr. Ganis Lukmandaru, S. Hut., M. Agr. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Young-age timbers from the community forest in Kulon Progo experiences the increasing demand for utilization. On the other side, the information with regard to the quality and variation within the properties of teak wood is limited to the consumers. The concentration of inorganic materials and acidity properties of the wood affects to its processing and utilization. This circumstance leads to the curiosity to address the properties of this kind of wood through the radial variation and site growth. The research used three trees in each three different site growth i.e. Kalibawang, Temon and Madiun. The samples used were 5 cm-thicknes disks that taken from the bottom side of the tree. The radial variation was divided into three different parts which were sapwood, outer and inner heartwood. The wood powder had been taken from each different part and was ground to 40-60 mesh in order to examine the ash content (ASTM 1102-56), acid insoluble ash content (TAPPI T 244 om88), inorganic element content (Ca, K, Mg, Na, Fe, Mn, dan Cu) and pH value. Data analysis was conducted using two-ways analysis of variance and HSD (Honesty Significant Difference). Pearson correlation was used to find the correlation among the parameters. The levels range of ash content and insoluble acid ash content of Kulon Progoâs teak are 0.65-2.99% and 0.34-2.39% respectively. The range of inorganic element content for Ca, K, Na, Mg, Fe and Cu are469,73 â 1447,33 ppm, 248,02 â 3760,50 ppm, 358,46 â 935,83 ppm, 559,01 â 1197,85 ppm, 0 â 31,14 ppm respectively, while the pH range is 5,66 â 6,27. The interaction between factors affects significantly the values of acid insoluble ash contents, and K content. The growth site affects significantly to the values of ash, Na and Ca content. Radial factor only affects the ash content. As defined by Pearson correlation analysis from all samples, it is found that strong correlation in the heartwood between the ash content and acid insoluble ash content (r = 0,92), while the ash content also has a significant correlation to K content (r = 0,87) in the sapwood. From the analysis is also measured that the K content has strong correlation to Na content (r = 0,67). However, the negative correlation was significantly found in the same part of wood for Na and Ca (r = - 0,60). The pH value is significantly correlated to the Ca content (r=0.41) in the data combination of the sap and heartwood parts.